Mean-Variance Analysis in the Theory of Liquidity Preference and Portfolio Selection - Feldstein, M. S. (Review of Economic Studies, 1969)
Journal Article Mean-Variance Analysis in the Theory of Liquidity Preference and Portfolio Selection Get access M. S. Feldstein M. S. Feldstein Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 1, January 1969, Pages 5–12, https://doi.org/10.2307/2296337 Published: 01 January 1969 Article history Received: 06 March 1967 Revision received: 27 June 1968 Published: 01 January 1969